Effect of aging and heat treatment on the optical properties of ZnS, SnS and Se thin films - Abdelrahman, Abubaker Elshiekh (2000)
Study on the optical properties of ZnS, SnS and Se thin films in polycrystalline and amorphous structure was carried out at room temperature. Double beam UV spectrophotometer was used to obtain the transmissions curve. The measurement of transmission for each sample was conducted in the range of 300 to 1100 nm, and the structures of samples were analyzed using X-ray diffraction spectrometer. Swanepoel (1983) method had been used in this study to determine the optical properties of the ZnS, SnS and Se thin films. Data from theoretical calculation was also used to cross-.check the validity of the optical data of the samples. The results show that the refractive index of the samples decreases as wavelength increases. The energy band gaps of the samples are in good agreement with the data reported in the literature previously. The results also show that the refractive index of the samples is thickness dependent. However, the energy band gaps for all the samples were found to be independent of film thickness in the range of 370 up to 742 run. While the energy band gaps of the Se thin films decreases with increasing film thickness. Three procedures of measurement were investigated for the samples. First, measurements were done immediately on the samples after they were deposited. Second, the measurement of the samples was done after they were exposed to the air. Third, the effect of annealing at different times in addition to different temperatures in ranging from (40 - 120) °C in ambient atmospheric pressure was studied. The results indicated that, the refractive index decreased with increasing the wavelength in all cases. Other results in the present study indicate that the aging have more significant effect on the refractive index, plasma energy and energy band gap of the ZnS and Se samples. Furthermore the refractive index and the energy band gap of the a-ZnS were not affected with the annealing time, while the energy band gap of the SnS was affected with annealing temperature.